An Empirical Analysis Of Mutual Fund Investments In The Vidarbha Region: Investor Vs. Broker Perspectives (Journal of Namibian Studies : History Politics Culture, 2023)
Looking at mutual fund investments in the Vidarbha area empirically, this research focuses on the contrasting viewpoints of investors and brokers. The study's overarching goal is to fill in the gaps in our knowledge on the selection of mutual funds, investing habits, and decision-making procedures for these two critical populations. Information was gathered from a statistically valid cross-section of Vidarbha's individual investors and financial brokers via in-depth interviews and surveying. Investors and brokers vary significantly in their risk perception, return expectations, and investing methods, according to the research. Contrasted with brokers' emphasis on diversity and market trends, investors often place a premium on a company's track record and reputation. Brokers, according to the report, tend to have more financial understanding than individual investors, highlighting the importance of financial literacy in influencing investing decisions. Furthermore, the effect of broker recommendations on investor choices is investigated, revealing a substantial impact, especially for novice investors. Market volatility and information asymmetry are two of the main obstacles highlighted by the study, which also offers solutions to improve investing results. In sum, the research sheds light on the dynamics of Vidarbha area mutual fund investments and provides useful information for brokers, investors, and lawmakers who want to create a more informed investing climate.